2011
DOI: 10.1017/s0025315411000609
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of spatial distribution of five species of mojarras (Actinopterygii: Gerreidae) in a small tropical estuary in south-eastern Brazil

Abstract: Patterns of spatial distribution of five species of mojarras (Actinopterygii: Gerreidae) in a small tropical estuary in south-eastern Brazil taynara pontes franco, leonardo mitrano neves, tatiana pires teixeira and francisco gerson arau ' joThe spatial patterns of distribution of five species of the Gerreidae (Diapterus rhombeus, Eucinostomus argenteus, Eucinostomus gula, Eucinostomus melanopterus and Eugerres brasilianus) in Mambucaba estuary, south-eastern Brazil, were determined to assess habitat partitioni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…This spatial separation is critical to the maintenance of mojarra populations, because different habitats influence abundance, growth, reproduction, recruitment and survival (Hajisamae et al, 2006). Similar spatial dynamics were reported for gerreids in tropical estuaries by Franco et al (2012) and Ramos et al (2014). Several studies in tropical areas have reported intrinsic changes in habitat preferences by juvenile fishes in response to local prey availability, predation risk and abiotic conditions (Gibson et al, 1998;Martino & Able, 2003;Johnston et al, 2007;Costa et al, 2012).…”
Section: Discussionmentioning
confidence: 59%
“…This spatial separation is critical to the maintenance of mojarra populations, because different habitats influence abundance, growth, reproduction, recruitment and survival (Hajisamae et al, 2006). Similar spatial dynamics were reported for gerreids in tropical estuaries by Franco et al (2012) and Ramos et al (2014). Several studies in tropical areas have reported intrinsic changes in habitat preferences by juvenile fishes in response to local prey availability, predation risk and abiotic conditions (Gibson et al, 1998;Martino & Able, 2003;Johnston et al, 2007;Costa et al, 2012).…”
Section: Discussionmentioning
confidence: 59%
“…), a positive tropical estuary (Teixeira & Helmer ; Franco et al . ) and in coastal lagoons (Andreata et al . , ; Rueda ).…”
Section: Discussionmentioning
confidence: 99%
“…The high abundance and distribution of this family in tropical and subtropical estuaries makes Gerreidae a good model with which to attempt to understand what drives patterns of spatial distribution in estuaries (Franco et al . ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…This species is particularly abundant in coastal lagoons in Mexico, Brazil and Cuba, where its capture in artisanal fisheries has an important socioeconomic role (Menezes and Figueiredo, ; Alvarez‐Lajonchère et al., ). Because of its euryhalinity (Eskinazi, ; Franco et al., ), omnivory (Menezes and Figueiredo, ) and high demand in local markets (Bezerra et al., ), E. brasilianus shows a high potential for aquaculture development, especially as an alternative to the monoculture of the shrimp Litopenaeus vannamei in coastal ponds. In north‐eastern Brazil, E. brasilianus has been reared historically in conjunction with the common snook Centropomus undecimalis and mullet Mugil liza since as early as the 1930s (Ihering, ).…”
Section: Introductionmentioning
confidence: 99%